UJI KESAMAAN BERKAS KOLIMATOR DENGAN VARIASI JARAK FFD (FOCUS FILM DISTANCE) PADA PESAWAT SINAR-X - Artitin, Cicillia; Nisa, Chairun; Sari, Oktavia Puspita; Anjarwati, Neneng (STIKES Syedza Saintika Padang, 2024)
The collimator is a part of the x-ray device that has the function of regulating the size of the field. If this field is not aligned, the anatomy that should enter the irradiation field is not exposed to radiation. The large number of exposures performed can result in a mismatch between the area of the irradiation field and the X-ray beam produced. Distance variations are used to determine the suitability or value of the shift in the collimator field area tested. This study aims to determine the feasibility of a collimator on an X-ray plane by determining the similarity of the collimated beam with the X-ray beam.The type of research used is quantitative with experimental methods in the radiology installation of Andalas University Hospital Padang in August 2023 with variations of FFD 90 cm, 100 cm, 110 cm, and 120 cm. The measuring instrument used collimator test tool with collimation size 14x18 cm using small focal spot and large focal sp-axis (horizontal) and Y-axis (vertical) values by not exceeding 3% of FFD (ΔX + ΔY ≤ 3% of FFD).The test results of the collimator beam similarity test with FFD distance variations that comply with the tolerance limit ≤ 2% FFD are at FFD 100 cm, 110 cm, and 120 cm when using a small focal spot. While those that do not match or exceed the tolerance limit ≤ 2% FFD are FFD 90 cm small focal spot, FFD 90 cm, 100 cm, 110 cm, and 120 cm when using a large focal spot. Collimation that is feasible to use in the radiographic imaging process on a small focal spot with a distance (FFD) starting from 100 cm. The large focal spot is not feasible to use and needs to be improved.Keywords: Conformity test, Beam collimation, FFD distance variation